ANALISIS ANGKA KEMATIAN NEONATAL DI PROVINSI BALI DENGAN PENDEKATAN ANALISIS REGRESI - SIHMAWATI, NI WAYAN DIAH; SUMARJAYA, I WAYAN; SUSILAWATI, MADE (E-Jurnal Matematika, 2018)
Neonatal mortality rate (NMR) is the number of infant death up to 28 days expressed in 1,000 live births in the same year. The aim of this research is to obtain the best model for NMR in Bali and to find significant factors that influence NMR in Bali using multiple linear regression and spatial regression methods. The data used in this study was obtained from the Health Departement in each district in Bali.The result shows that there is no spatial dependence between regions and no interregional heterogeneity. This suggests that spatial regression is not applicable in this study. Hence, we model the NMR using multiple linear regression. Furthermore, we obtained the estimated NMR model in Bali is . In conclusion, the factors that influence the NMR are the percentage of babies with low weight and percentage of households with a clean and healthy living behavior.